Coculture of Endothelial Cells with Human Pluripotent Stem Cell‐Derived Cardiac Progenitors Reveals a Differentiation Stage‐Specific Enhancement of Cardiomyocyte Maturation. Issue 8 (14th May 2019) - Dunn, Kaitlin K.; Reichardt, Isabella M.; Simmons, Aaron D.; Jin, Gyuhyung; Floy, Martha E.; Hoon, Kelsey M.; Palecek, Sean P.
Abstract : Cardiomyocytes (CMs) generated from human pluripotent stem cells (hPSCs) are immature in their structure and function, limiting their potential in disease modeling, drug screening, and cardiac cellular therapies. Prior studies have demonstrated that coculture of hPSC‐derived CMs with other cardiac cell types, including endothelial cells (ECs), can accelerate CM maturation. To address whether the CM differentiation stage at which ECs are introduced affects CM maturation, the authors coculture hPSC‐derived ECs with hPSC‐derived cardiac progenitor cells (CPCs) and CMs and analyze the molecular and functional attributes of maturation. ECs have a more significant effect on acceleration of maturation when cocultured with CPCs than with CMs. EC coculture with CPCs increases CM size, expression of sarcomere, and ion channel genes and proteins, the presence of intracellular membranous extensions, and chronotropic response compared to monoculture. Maturation is accelerated with an increasing EC:CPC ratio. This study demonstrates that EC incorporation at the CPC stage of CM differentiation expedites CM maturation, leading to cells that may be better suited for in vitro and in vivo applications of hPSC‐derived CMs. Abstract : A roadblock facing the use of human pluripotent stem cell‐derived cardiomyocytes (hPSC‐CMs) in regenerative therapies and in vitro assays is the inability to generate functionally mature, adult‐like cells. Here, the authors ask whether cues from developing hPSC‐derived endothelial cells (ECs) influence maturation of hPSC‐CMs during coculture. The ECs accelerate structural and functional maturation when cocultured with hPSC‐derived cardiac progenitors but have little effect on fully differentiated hPSC‐CMs, indicating stage‐specific effects of hPSC‐derived ECs on hPSC‐CM maturation.